The Effect of Ethnobotanical Project Based Learning-STEM Model on Students 21st Century Thinking Skills in Science Learning - Tomi Apra Santosa; Heppy Sapulete; Siti Fatimah Hiola; Dewanto Dewanto; Aat Ruchiat Nugraha; Everhard Markiano Solissa; Nurina Happy; Anwar Manahor (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the influence of ethnobotanically charged project-based learning-STEM models on students' critical thinking skills in biology learning. This type of research is a meta-analysis research. The inclusion criteria in this study are that the research must be relevant; research data was obtained from Google Scholar, Mendeley, ScienceDirect, ERIC and ProQuest; Research must be indexed by SINTA or Scopus, research published in 2023-2025 and have complete data to obtain effect size values. Data analysis with the help of the Jamovi application to calculate the effect size value, publication bias and homogeneity test. The results of this study concluded that the value of the summary effect size (d = 1.129; p < 0.005; Z = 9.890). These findings explain that there is an influence of the ethnobotanically charged project-based learning-STEM model on students' 21st-century skills in Science Learningcompared to the conventional model with a strong effect size category.